2020
DOI: 10.1002/lsm.23334
|View full text |Cite
|
Sign up to set email alerts
|

Early Treatment Effects of Nonablative Fractional Lasers (NAFL) on Hypertrophic Scars in an Animal Model

Abstract: Background and Objectives Recently, there have been several attempts to apply the laser therapy to hypertrophic scars (HTS). In particular, the fractional laser is in the spotlight for its usefulness in rapid wound healing and dermal remodeling. However, most previous studies have focused on the ablative fractional laser (AFL), and there are no studies on the mechanism of the nonablative fractional laser (NAFL) effect in HTS treatment. In this study, we aimed to evaluate the changes in histology and molecular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…Using fractional lasers for scars has several advantages (rev. in [ 25 ]). Heating the dermis to 50–70 °C, irradiation with a laser produces ~3 mm deep microscopic skin lesions, initiating rapid wound healing in the affected area.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using fractional lasers for scars has several advantages (rev. in [ 25 ]). Heating the dermis to 50–70 °C, irradiation with a laser produces ~3 mm deep microscopic skin lesions, initiating rapid wound healing in the affected area.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent paper, Chung et al [ 25 ] reported that the AFL and NAFL treatment of pigs significantly changed the expression of Mmp2 and Mmp9. In ELISA experiments, the authors showed that the level of Mmp2 significantly increased after low- and high-energy NAFL treatment compared to the sham control and AFL treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In turn, the differences between the sham control and AFL, according to the authors, were insignificant. In qPCR experiments, Chung et al [11] did not see significant differences between groups treated with AFL and any group treated with NAFL. Contrarily, the expression of Mmp2 in ALF-treated animals significantly exceeded one in sham control.…”
Section: Ofmentioning
confidence: 90%
“…In our study (Figure 3), we show significant suppression of Mmp2 at the early stages of post-therapeutic recovery. Respectively, the following increase in the expression of Mmp2 would explain the absence of statistical differences in Chung's qPCR experiments [11] and the accumulation of secreted Mmp2 detectable by ELISA. The same hypothesis can explain higher levels of Mmp2 in animals treated with low and high-energy NAFL.…”
Section: Ofmentioning
confidence: 98%
See 1 more Smart Citation